Effect of "El Niño 1997-98" phenomenon in landing of artisanal fishery resources of Salaverrv (Trujillo) - Tresierra-Aguilar, Alvaro (1999)
The landing volumes of artisanal fishery are analyzed in Salaverry Port, before, during and after "El Niño 1997-98" phenomenon. The landings during the first phase of "El Niño" were about of 1000 tm in 1996 and it increased to 17000 tm in 1997. The presence of tropical water species with “El Niño” event were high in the first semester of 1998, they are increased in fishery and more than 50% of landings corresponded to Coryphaena hippurus. Later on, the usual landing volumes and traditional species returned with normalization of environmental condition. The socioeconomic impact is also analyzed